Rules Are Made to Be Broken, or the Menuetto of Beethoven’s Op. 2, No. 1 (Orfeu, 2021)
A striking gesture appears at the climax of the first phrase of the Menuetto from Ludwig van Beethoven’s Sonata for Piano in F minor, Op. 2, No. 1. This motivic gesture, which may be understood as derived from manipulation of standard voice-leading procedures, has intriguing ramifications that deeply affect the structure and narrative of the entire movement. These features are explored with the aid of Schenkerian analytic procedures, and the analysis is then compared to an interpretation of this same movement by Heinrich Schenker.
Keywords: Beethoven; motive; Schenkerian analysis; Tonwille